"High Frequency/Small Tidal Volume Differential Lung Ventilation": A Technique of Ventilating the Nondependent Lung of One Lung Ventilation for Robotically Assisted Thoracic Surgery. (12th August 2015) - Shoman, Bassam M.; Ragab, Hany O.; Mustafa, Ammar; Mazhar, Rashid
Abstract : With the introduction of new techniques and advances in the thoracic surgery fields, challenges to the anesthesia techniques had became increasingly exponential. One of the great improvements that took place in the thoracic surgical field was the use of the robotically assisted thoracic surgical procedure and minimally invasive endoscopic thoracic surgery. One lung ventilation technique represents the core anesthetic management for the success of those surgical procedures. Even with the use of effective one lung ventilation, the patient hemodynamics and respiratory parameters could be deranged and could not be tolerating the procedure that could compromise the end result of surgery. We are presenting our experience in managing one patient who suffered persistent hypoxia and hemodynamic instability with one lung ventilation for robotically assisted thymectomy procedure and how it was managed till the completion of the surgery successfully.